Geomagnetic Kp Index and Planetary Magnetosphere Size Relationship: for Mercury and Jupiter During two Types of Geomagnetic Conditions (Baghdad Science Journal, 2020)
Kp index correlates with the many magnetosphere properties, which are used to measure the level of magnetic activity. In the solar system, the two different planets, Mercury with weak magnetic field and Jupiter with strong magnetic field, are selected for this study to calculate the planet's magnetosphere radius (RMP) which represents the size of magnetosphere compared with solar activity through Kp index, through two types of geomagnetic conditions; quiet and strong for the period (2016-2018). From the results, we found that there are reversible relations between them during strong geomagnetic storms, while there are direct relations during quiet geomagnetic conditions. Also it is found that there is a reduction in the size of magnetosphere during the strong geomagnetic storms as compared to the magnetosphere size during geomagnetic quiet conditions for the two planets: Mercury and Jupiter. We can conclude from these results that the relation between storm type and magnetosphere size is independent of the strength of planetary surface magnetic field and their distance from the Sun.